Capital Market Investment Education to Strengthen The Financial Literacy of Karang Taruna - Citra Andriani; Asih Niati; Tri Rinawati; Naini Rizka Amalia (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2026)
This community service program was conducted to enhance financial literacy, particularly in basic understanding and skills related to capital market investment, among members of Karang Taruna Wiradiranda. The activities were implemented through the delivery of educational materials covering an introduction to the capital market, explanations of various investment instruments, an understanding of potential returns and risks, and simple exercises in investment decision-making. The program's effectiveness was assessed using pre- and post-tests administered to participants before and after the socialization activities. The evaluation results indicated an improvement in participants’ understanding of capital market investment, as reflected in higher post-test scores than pre-test scores. In addition, the program fostered increased interest and self-confidence among participants in developing more rational and responsible investment plans. The implementation method employed an educational–participatory approach comprising several stages: identification of participants’ needs; socialization of basic financial literacy and capital market concepts; practical investment training through simulations and the use of investment applications; and ongoing mentoring. Program evaluation was also carried out through discussions and observations of participants’ levels of understanding and engagement throughout the activities. The results demonstrated improved participant comprehension of fundamental investment concepts, capital market mechanisms, and technical skills in operating investment applications. Furthermore, participants showed greater interest and readiness to initiate independent investment activities. This program is expected to serve as an initial step in fostering wiser, sustainable financial behavior oriented toward long-term financial planning.